2015
DOI: 10.1149/2.0401603jes
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Liquid Water Saturation in Gas Diffusion Layers by X-Ray Tomographic Microscopy

Abstract: Performance and durability of polymer electrolyte fuel cells are closely related to the water management. In gas diffusion layers (GDL), the presence of liquid water is associated with mass transport losses. For optimization of the materials, mechanisms and parameters influencing the water saturation have to be understood. Ex-situ water injection and withdrawal experiments, allowing for well-defined boundary conditions, have been performed with three different GDL materials, using X-ray tomographic microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 28 publications
2
83
0
Order By: Relevance
“…The size distributions shown in Fig. 13 are in good agreement with accepted values for similar materials [59][60][61][62].…”
Section: Fibrous Mediasupporting
confidence: 84%
“…The size distributions shown in Fig. 13 are in good agreement with accepted values for similar materials [59][60][61][62].…”
Section: Fibrous Mediasupporting
confidence: 84%
“…Spatial and temporal resolutions in X-ray computed tomography are now sufficiently high, so that even the evolution of liquid water at the pore scale can be captured with in-situ/operando experiments (e.g. with subsecond time lapse tomography) [12][13][14][15]. It was demonstrated that these advanced tomography experiments are the basis to understand saturation dependent effective properties in wet GDL [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the gas diffusivity, the experimental evidence for the anisotropy of permeability is controversial. Some groups presented evidence for higher inplane permeability [26,27], whereas others argued for higher permeability in the through-plane direction [14], which they explained with smaller bottleneck dimensions in the in-plane direction. At this stage it is not clear why for example the narrow in-plane bottlenecks should only limit in-plane permeability and why they would not also limit the in-plane diffusivity?…”
Section: Introductionmentioning
confidence: 99%
“…Lamibrac et al recently extracted pore size distribution for SGL and Toray materials using XTM data. 47 They demonstrated that SGL 24BA presents a much broader pore size distribution compared to Toray TGP-H-060. Additionally, SGL contains a notable number of rather wide pores (range of 200 μm diameter) which do not exist in the Toray or Freudenberg materials.…”
Section: Resultsmentioning
confidence: 99%
“…[40][41][42][43][44][45][46] Recently, Lamibrac et al developed a setup compatible with X-ray tomographic microscopy (XTM) imaging to perform MSP measurements. 47 Compared to previous attempts, 48,49 the recent developments in terms of image processing and segmentation allowed extraction of quantitative P C (S) data from the XTM images.…”
Section: 35mentioning
confidence: 99%